2022
DOI: 10.5935/jetia.v8i36.820
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the major contractors’ selection criteria and their impacts in civil engineering construction projects

Abstract: Construction projects in especially developing countries are characterised by failure to meet project baselines (time, cost, quality). This is worsened by the inefficiencies in the application of contractors' selection criteria during the bidding processes of both civil and building construction projects. The application of contactor section criteria and their benefits in civil engineering projects is an area that is underexplored in construction management literature in the Nigerian context. This study aims t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
0
0
0
Order By: Relevance
“…Each of these main criteria has its own sub-criteria as shown in Table 5. The study done by Okereke et al (2022) has shown that three important factors in contractor selection are managerial capability and competent supervisory staff, technical ability and financial soundness. Another important factor in choosing contractors for civil engineering projects is the bid price.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Each of these main criteria has its own sub-criteria as shown in Table 5. The study done by Okereke et al (2022) has shown that three important factors in contractor selection are managerial capability and competent supervisory staff, technical ability and financial soundness. Another important factor in choosing contractors for civil engineering projects is the bid price.…”
Section: Literature Reviewmentioning
confidence: 99%